THE USE AND SOCIAL SIGNIFICANCE OF SLANGS IN THE UZBEK LANGUAGE (The Conference Hub, 2025)
The article discusses the factors of emergence, use, role and significance of slang in the communication process, which is considered a limited lexical unit. The study of slang from the point of view of linguistics, its lexical and semantic features, its spread through modern information technologies, as well as their impact on the development of culture and language are discussed.